Influence of iron addition on the microstructure and the electrochemical corrosion of Al-Zn-Mg alloys - Benedetti, Assis Vicente [UNESP]; Cabot, P. L.; Garrido, J. A.; Moreira, A. H. (Kluwer Academic Publ, 2001)
The effect of Fe addition on the microstructural properties and the corrosion resistance of Al-Zn-Mg alloys submitted to different heat treatments (cast, annealed and aged), has been studied in chloride solutions using optical microscopy (OM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray (EDX), cyclic polarization (CP) and open circuit potential (o.c.p.) measurements. The presence of 0.3% Fe in the alloy limited the growth of the MgZn2 precipitates, both in the annealed and in the quenched specimens. No effect of Cr on the grain size in the presence of Fe was found because of the accumulation of Cr in the Fe-rich particles. Fe in the Al-Zn-Mg alloys also made them more susceptible to pitting. Pitting occurred mainly near the Fe-rich particles both, under o.c.p. conditions in O-2-saturated solutions and during the CP.
Keywords: aluminium-based alloys; corrosion; heat treatment